The last of the Mohicans [videorecording (DVD)] - Mann, Michael, 1943-; Day-Lewis, Daniel; Stowe, Madeleine; Hoenig, Dov; Cooper, James Fenimore, 1789-1851 (Twentieth Century-Fox Home Entertainment, 1999)
"An epic adventure and passionate romance unfold against the panorama of a frontier wilderness ravaged by war. Academy award winner Daniel Day-Lewis stars as Hawkeye, rugged frontiersman and adopted son of the Mohicans, and Madeleine Stowe is Cora Munro, aristocratic daughter of a proud British Colonel. Their love, tested by fate, blazes amidst a brutal conflict between the British, the French and Native American allies that engulfs the majestic mountains and cathedral-like forests of Colonial America"--Container.